1983
DOI: 10.1038/bjc.1983.58
|View full text |Cite
|
Sign up to set email alerts
|

Radioprotection by WR-2721 in vitro at low oxygen tensions: Implications for its mechanisms of action

Abstract: Summary Radioprotection of spheroids of Chinese hamster V79 cells by WR-2721 was found to be a function of spheroid size, with the greatest dose-modifying effect by the protector observed for spheroids almost large enough to contain radioresistant "anoxic" cells. The nature of the response suggested that most of the protective effect was due to the presence of an increased hypoxic fraction in the drug-treated spheroids. Similarly, when single-cell suspensions were irradiated at various oxygen tensions, one co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…It has been suggested that WR-1065 can react rapidly with oxygen in the culture medium, leading to a state of transient hypoxia (Purdie et al, 1983;Durand, 1983;Biaglow et al, 1984). This could partially explain the reduction in DSB DNA damage reported in the present study.…”
Section: Double-strand Break Formationsupporting
confidence: 75%
“…It has been suggested that WR-1065 can react rapidly with oxygen in the culture medium, leading to a state of transient hypoxia (Purdie et al, 1983;Durand, 1983;Biaglow et al, 1984). This could partially explain the reduction in DSB DNA damage reported in the present study.…”
Section: Double-strand Break Formationsupporting
confidence: 75%
“…An important factor that has been demonstrated to exert a major influence on the extent of amifostine protection is the oxygen concentration at the time of irradiation (38,39). Several in vivo experiments have been carried out to measure the extent of normal tissue protection by amifostine over a wide range of inspired oxygen concentrations (26,33,34,36,37,40).…”
Section: Discussionmentioning
confidence: 99%
“…Dimethyl sulfoxide (1%) was toxic to cells by itself and also increased HSP synthesis (not shown). The only compound tested that we found effective in preventing erythrophagocytosis-induced synthesis of stress proteins was the free thiol WR-1065 (dephosphorylated from the radioprotective agent WR-2721) (27,28). WR-1065 inhibited induction of HSP70 and p32 during erythrophagocytosis (Fig.…”
mentioning
confidence: 99%
“…5). Because WR-1065 can act in thiol disulfide exchange reactions and substitute for glutathione as hydrogen donor (28), the protective effects of WR-1065 suggest a role for glutathione depletion in the induction of stress proteins during erythrophagocytosis. Indeed, one common property attributed to the various inducers of p32/heme oxygenase is reactivity toward sulfhydryl groups and depletion in cellular glutathione (18,19,29).…”
mentioning
confidence: 99%